International collaboration of VIR as an important factor of replenishing the collection of grain legume genetic resources - M. A. Vishnyakova; T. G. Alexandrova; T. V. Buravtseva; M. O. Burlyaeva; G. P. Egorova; E. V. Semenova; I. V. Seferova; I. L. Stepanova; I. I. Yankov (Труды по прикладной ботанике, генетике и селекции)
The percentage of foreign material in the VIR collection of grain legumes varies from 42% (vetch) to 96-97% (cowpea, chickpea). For most crops, this indicator is between 75-86%. It depends either on the agroclimatic needs of the crops reflecting the areas of their cultivation and growth over the world or on their centers of origin as well as on the scale of their production and breeding in different countries. The main way of receiving new crop material from abroad is VIR's international cooperation which was initiated by N. I. Vavilov. Since then, interaction of the Institute with foreign partners has not lost its relevance and traditions. The sources of foreign material are international collecting expeditions, the exchange of scientists, requests for germplasm to international genebanks, national botanical gardens, breeding organizations, specialized research institutions and universities. The most important tool for obtaining foreign material was and still is the exchange of germplasm samples. This article provides an overview of the ways by which foreign material has entered the VIR collection of grain legumes over the last 20 years. During this period, the total of 7552 foreign accessions has been added to the collection, which makes 16% of its overall volume. The main sources of such material are international genebanks and national centers working with plant genetic resources. For the collections containing crop wild relatives (CWR), botanical gardens remain important suppliers of material. The main partner countries that have participated in mutually beneficial partnerships and germplasm exchange with VIR are Syria, China, the USA, Canada, Ukraine, Belarus, France, and Australia. International expeditions have been and remain a fruitful source of local varieties and CWR. Of undoubted interest, along with the modern and local varieties coming from abroad, are wild species of such crops as soybean, chickpea and lentil whose areas of distribution lie beyond the borders of this country. Such species are promising for introgressive breeding. The study of new foreign accessions within VIR's network made it possible to identify sources of economically valuable traits for the main trends of crop breeding.